Affecting Change in Exercise Behavior Following the Transtheoretical Model (TTM) of Stages of Behavior Change - Mattayakorn, Korada (Academic Journal of Thailand National Sports University, 2018)
It is found that current situations in the world and in Thailand health problems are caused by in appropriate health behavior of the people leading to non-communicable diseases (NCD) such as obesity, diabetes, hypertension and cardiovascular diseases. These health risks are some of the leading causes of death today. Some main risk factors which contribute to the causes of chronic NCD are irregular exercise, lack of exercise, and unhealthy eating habits. It is thusessential to encourage people to realize thei mportance of regular exercise so that they change their behavior in a consistent and lasting way. Trans the roretical Model (TTM) is designed to help people change their habit patterns by focusing on their process of change and decision making in over coming addictions to alcohol and cigarettes. Later on, Marcus and his team expanded the scope of Prochaska’s model and applied it to changing exercise behavior, explaining that people are unable to change their habit patterns all at once, but rather need to gradually adjust their whole thought process about the change, step by step. The TTM model consists of 1) Stages of change in behavior, divided into 5 stages: Pre-contemplation, Contemplation, Preparation, Action and Maintenance; 2)Self-Efficacy; 3) Decisional balance, and 4) Processesof change. In this study, the researcher will apply TTM to affect change in exercise behavior of individuals. As a theoretical base,TTM provides aunique and practical model, as it is structured in a way that suits individuals of both sexes and all ages, and is an effective tool both for making predictions and bringing about real change in exercise behavior.